The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3389/fncom.2014.00098
|View full text |Cite
|
Sign up to set email alerts
|

T-type calcium channels promote predictive homeostasis of input-output relations in thalamocortical neurons of lateral geniculate nucleus

Abstract: A general theory views the function of all neurons as prediction, and one component of this theory is that of “predictive homeostasis” or “prediction error.” It is well established that sensory systems adapt so that neuronal output maintains sensitivity to sensory input, in accord with information theory. Predictive homeostasis applies the same principle at the cellular level, where the challenge is to maintain membrane excitability at the optimal homeostatic level so that spike generation is maximally sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 71 publications
(218 reference statements)
4
27
0
Order By: Relevance
“…Burst and tonic response modes are often described as binary states, which is an accurate description for the extreme ends of behavioral arousal: tonic mode during active sensory processing and burst mode during sleep and anesthesia. This hard distinction, however, fails to capture thalamic processing during the transition between the two response modes (Deleuze et al, 2012;Hong et al, 2014). In between the extremes of focused sensory processing and slow-wave sleep, the graded deinactivation of the T-channels of a cell may play a previously underappreciated role in visual processing (Mease et al, 2017).…”
Section: Thalamic Burst Mode and Behavioral Statementioning
confidence: 99%
See 1 more Smart Citation
“…Burst and tonic response modes are often described as binary states, which is an accurate description for the extreme ends of behavioral arousal: tonic mode during active sensory processing and burst mode during sleep and anesthesia. This hard distinction, however, fails to capture thalamic processing during the transition between the two response modes (Deleuze et al, 2012;Hong et al, 2014). In between the extremes of focused sensory processing and slow-wave sleep, the graded deinactivation of the T-channels of a cell may play a previously underappreciated role in visual processing (Mease et al, 2017).…”
Section: Thalamic Burst Mode and Behavioral Statementioning
confidence: 99%
“…When this occurs, depolarizing stimuli can activate T-channels to generate a Ca 2ϩ potential (T-potential), which can then trigger a short train of high frequency, Na ϩ -based action potentials. It is important to note that the magnitude of the T-potential and subsequently the number of spikes it triggers depend on the percentage of T-channels in the deinactivated versus the inactivated state, which, in turn, depends on the depth and duration of the preceding hyperpolarization (Deschênes et al, 1984;Destexhe and Sejnowski, 2002;Hong et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The theory should predict the properties of voltage-gated ion channels as it did IPSG. For example, the theory correctly predicted the experimental observation that T-type calcium channels are homoeostatic in counterbalancing opponent IPSG in thalamocortical neurons of LGN50. The more general theory proposes differences between sensory and motor neurons, and it correctly predicted evidence that T-type calcium channels are not homoeostatic but cause bursts of spikes in motor thalamus51.…”
Section: Discussionmentioning
confidence: 73%
“…We previously tested this by examining the function of T-type calcium channel (TtCC) in thalamocortical (TC) neurons of the lateral geniculate nucleus (LGN) while mimicking natural conditions. We found that TtCC amplified EPSPs toward spike threshold so that EPSPs may or may not cause spikes, depending on their amplitude ( Hong et al, 2014 ). This supports our theory, according to which TtCC in sensory neurons should help to maximize the causal link between synaptic excitation and spikes without themselves causing spikes, through a process we have termed “predictive homeostasis” ( Fiorillo et al, 2014 ; Hong et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that TtCC amplified EPSPs toward spike threshold so that EPSPs may or may not cause spikes, depending on their amplitude ( Hong et al, 2014 ). This supports our theory, according to which TtCC in sensory neurons should help to maximize the causal link between synaptic excitation and spikes without themselves causing spikes, through a process we have termed “predictive homeostasis” ( Fiorillo et al, 2014 ; Hong et al, 2014 ). In this model of a sensory neuron, TtCC are one of many voltage-gated ion channel (VGC) subtypes predicting and counteracting sensory-related synaptic drive so that each spike signals a positive prediction error, in the spirit of “predictive coding” (e.g., Barlow, 1961 ).…”
Section: Introductionmentioning
confidence: 99%